Method for preparing silicon tetrafluoride by pyrolyzing sodium fluosilicate
By pretreating the pyrolysis reaction method of activated sodium fluorosilicate and additives, the problem of low adhesion wall agglomeration and conversion efficiency of material in the fluorosilicate pyrolysis process is solved, and the efficient preparation and high efficiency of silicon tetrafluoride are achieved. Purification of purity reduces production costs and environmental pollution, and recycles residues.
Patent Information
- Application Number
- CN202411403527.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-11
AI Technical Summary
In the existing fluorosilicate pyrolysis process, there are problems of material adhesion wall agglomeration and low conversion efficiency, resulting in a large amount of impurity components of silicon tetrafluoride and high difficulty in purification.
By pretreating activated sodium fluorosilicate and additives, their activity and specific surface area are improved, and combined with process control, a pyrolysis reaction is carried out to prepare silicon tetrafluoride.
It significantly reduces the agglomeration and wall adhesion of the material during the pyrolysis process, improves the decomposition and conversion efficiency, simplifies the purification process of silicon tetrafluoride, reduces production costs and environmental pollution, and realizes the recycling and utilization of residues.
Smart Images

Figure CN119409197A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical industry and electronic special gases, and in particular relates to a method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate. Background Art
[0002] Silicon tetrafluoride is widely used in the electronics and semiconductor industries. It is an important raw material for the preparation of high-purity fluorosilicic acid and silane, crystalline silicon, optical fiber, etc. It can also be used to prepare cement and artificial marble hardeners. With the rapid development of industries such as polysilicon, silicon tetrafluoride has a large market demand space and has broad application prospects in the microelectronics industry. At present, several methods for preparing silicon tetrafluoride using fluorosilicates have been disclosed in existing documents or patents. The patent application number CN101948114A applied by Yunnan Chemical Research Institute uses the method of sulfuric acid acidification of sodium fluorosilicate to prepare silicon tetrafluoride and anhydrous hydrogen fluoride; the patent application number CN111039293A applied by Duofuduo Chemical Co., Ltd. uses dry fluorosilicates to prepare silicon tetrafluoride by pre-decomposition and calcination; the patent application number CN101698482A applied by Xi'an Sanrui Industrial Co., Ltd. uses a reactor to pyrolyze sodium fluorosilicate to prepare silicon tetrafluoride. The methods described in these patents are mostly mixtures of multiple substances, with complex ingredients and high costs. The silicon tetrafluoride produced has many impurities and complex types, and is difficult to purify. There are also problems such as wall sticking and low conversion efficiency.
[0003] In view of this, it is necessary to provide a new preparation method to solve the problems of material sticking to the wall and agglomeration and low conversion efficiency in the existing pyrolysis process. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate. The present invention obtains a raw material with high activity and high specific surface area through pre-treatment activation, and combined with the process control described in the present invention, significantly reduces the phenomenon of material agglomeration and wall adhesion during pyrolysis, and greatly improves the decomposition and conversion efficiency of the raw material. In addition, the prepared silicon tetrafluoride gas has a simple composition and a small number of impurities, and is easy to be subsequently purified to prepare high-purity silicon tetrafluoride. At the same time, the present invention can also recycle and process pyrolysis residues, thereby achieving full utilization of resources. This invention not only improves the stability of the pyrolysis process, but also reduces production costs, reduces environmental pollution and recovers useful resources, thereby reducing the environmental burden and economic pressure of enterprises, and has important environmental, economic and social significance.
[0005] The purpose of the present invention is achieved through the following technical solutions: A method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate comprises the following steps: (1) Sodium fluorosilicate and the additive are crushed and sieved separately, and then activated at 250-620°C; (2) The activated sodium fluorosilicate and the auxiliary agent are mixed and subjected to a pyrolysis reaction to obtain a crude silicon tetrafluoride product and residual solids; the crude silicon tetrafluoride product is purified to obtain a silicon tetrafluoride product.
[0006] Preferably, in step (1), the auxiliary agent is any one of calcium fluoride, magnesium fluoride, barium fluoride, white carbon black and silicon carbide.
[0007] Preferably, in step (1), the sodium fluorosilicate is crushed and then passed through a 60-120 mesh sieve.
[0008] Preferably, in step (1), the additive is crushed and then passed through a 200-300 mesh sieve.
[0009] Preferably, in step (1), the activation treatment pressure is -20 kPa to -10 kPa (G), and the activation treatment time is 3 to 8 hours. The moisture content of the material after activation treatment is 250 to 300 ppm, and the specific surface area is 350 to 550 m 2 / g.
[0010] Preferably, in step (2), the activated sodium fluorosilicate and the auxiliary agent are mixed in a mass ratio of 4 to 5: 1. The mixed addition amount of the activated sodium fluorosilicate and the auxiliary agent accounts for 2% to 10% of the reactor fullness.
[0011] Preferably, in step (2), the conditions for the pyrolysis reaction are: pyrolysis temperature of 550 to 650° C., reaction pressure of -10 kPa to 10 kPa (G), and pyrolysis time of 1.5 to 3.0 h.
[0012] Preferably, the residual solid is prepared into a suspension, and the fluorosilicic acid solution is added and stirred for reaction, and the sodium fluorosilicate obtained by filtration, washing and drying is reused in step (1).
[0013] Preferably, the specific operation of preparing the residual solid into a suspension includes: mixing the residual solid with water in a mass ratio of 1:2.5-4 to prepare a suspension.
[0014] Preferably, the mass ratio of the fluorosilicic acid solution to the residual solids is 8 to 12:1.
[0015] Preferably, the concentration of the fluorosilicic acid solution is 10 to 15 wt %.
[0016] Preferably, the addition of the fluorosilicic acid solution is completed within 2 to 5 hours.
[0017] Preferably, the stirring reaction rate is 40 to 90 r / min, and the stirring reaction time is 3 to 6 h.
[0018] Preferably, the drying temperature is 100-150° C., and the drying time is 3-6 hours.
[0019] The role of the auxiliary agent described in the present invention: Although the auxiliary agent does not directly participate in the chemical reaction, its role is reflected in two aspects. First, during the pyrolysis process, the auxiliary agent can help disperse the material, prevent the generated sodium fluoride from melting and forming a hard lump under high temperature conditions, and then avoid adhering to the wall of the reactor or forming a phenomenon of wrapping the material, all of which may reduce the decomposition efficiency. Secondly, the auxiliary agent can also provide additional surface decomposition reaction sites, which is equivalent to increasing the specific surface area of the material. Using an auxiliary agent is a more common method.
[0020] Compared with the prior art, the beneficial effects of the present invention include: (1) The present invention solves the wall sticking and agglomeration problems that occur in the process of preparing silicon tetrafluoride by pyrolysis of fluorosilicate, thereby significantly improving the decomposition efficiency. In addition, the prepared silicon tetrafluoride gas has fewer impurity components, which effectively simplifies the subsequent purification process and reduces the corresponding technical difficulty and cost.
[0021] (2) The residual solid materials generated in the pyrolysis process of the present invention can be recycled, and no fluorine-containing waste is generated in the process flow, thereby significantly reducing the impact on the environment. This improvement is not only conducive to achieving sustainable environmental development, but also has obvious environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The XRD spectra of the solid residual material in step (2) of Example 1 and the mixture after the solid residual material in step (3) reacts with the fluorosilicic acid solution; wherein the CaF2 pyrolysis residue corresponds to step (2), and the CaF2 residue synthesis corresponds to step (3).
[0023] Figure 2 The XRD spectra of the solid residual material in step (2) of Example 2 and the mixture after the solid residual material in step (3) reacts with the fluorosilicic acid solution; wherein the MgF2 pyrolysis residue corresponds to step (2), and the MgF2 residue synthesis corresponds to step (3).
[0024] Figure 3 The XRD spectra of the solid residual material in step (2) of Example 3 and the mixture after the solid residual material in step (3) reacts with the fluorosilicic acid solution; wherein the BaF2 pyrolysis residue corresponds to step (2), and the BaF2 residue synthesis corresponds to step (3).
[0025] Figure 4The XRD spectra of the solid residual material in step (1) of comparative example 1 and the mixture after the solid residual material in step (2) reacts with the fluorosilicic acid solution; wherein, "pyrolysis residue without adding auxiliary agent" corresponds to step (1), and "synthesis of Na2SiF6" corresponds to step (2).
[0026] Figure 5 The XRD spectra of the solid residual material in step (1) of comparative example 1 and the mixture after the solid residual material in step (2) reacts with the fluorosilicic acid solution; wherein, "pyrolysis residue without adding auxiliary agent" corresponds to step (1), and "synthesis of Na2SiF6" corresponds to step (2).
[0027] Figure 6 The XRD spectra of the solid residual material in step (1) of comparative example 1 and the mixture after the solid residual material in step (2) reacts with the fluorosilicic acid solution; wherein, "pyrolysis residue without adding auxiliary agent" corresponds to step (1), and "synthesis of Na2SiF6" corresponds to step (2).
[0028] Figure 7 This is a photo of the solid residue in step (2) of Example 1.
[0029] Figure 8 This is a photo of the solid residual material in step (1) of comparative example 1. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The sodium fluorosilicate raw material described in the following examples and comparative examples is industrial sodium fluorosilicate, wherein the arsenic content thereof shall not exceed 1 mg / kg.
[0032] Example 1 A method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate, comprising the following steps: (1) Take an industrial grade sodium fluorosilicate sample with a particle size D80 of 100 mesh (after crushing and sieving), activate it at a temperature of 330°C and a vacuum degree of -20kpa to -10kpa for 6 hours, and then weigh 5000g of the sample; take an analytical pure calcium fluoride sample with a particle size D80 of 250 mesh (after crushing and sieving), activate it at a temperature of 600°C and a vacuum degree of -20kpa to -10kpa for 6 hours, and then weigh 1000g of the sample; (2) After the weighed 5000g sample and 1000g sample were evenly mixed, they were put into a rotary furnace at a rate of 1000g / h for pyrolysis reaction. The rotary furnace was set to a temperature of 625°C, -10kpa to -5kpa, and the material stayed in the furnace tube for 2.5h. After the reaction was completed, the solid residual material was cooled to room temperature and weighed to 3158.4g. The sodium fluorosilicate content was 0.35% after sampling and analysis. The solid residual material was loose and had no agglomeration phenomenon, and there was no wall adhesion in the rotary furnace. The generated silicon tetrafluoride gas was collected with an air bag after dust removal and water removal by concentrated sulfuric acid.
[0033] In step (2), the silicon tetrafluoride gas collected by the air bag is first purified by passing it through an adsorption column containing 4A molecular sieve and granular activated carbon, and then the gas is introduced into a low-temperature freezing device that has been cooled to -115°C. After the intake is completed, the temperature is kept for 2 hours, and then the temperature is slowly raised to -92°C and the gas is collected. Finally, the impurity content is detected by gas chromatography, and the results show that the purity of the silicon tetrafluoride gas is 99.92%.
[0034] (3) Take 700g of solid residual material, add 2100g of pure water to make a suspension, stir at a rate of 60r / min for 1h, then slowly add 6000g of fluorosilicic acid solution, the concentration of fluorosilicic acid solution is 13wt%, the addition time is 2h, continue to stir and react for 2h after the addition is completed, then filter and separate and wash, dry at 120℃ for 3h, weigh 1086.5g after cooling, and take a sample for analysis. XRD analysis shows that the substance is a mixture of sodium fluorosilicate and calcium fluoride, with a sodium fluorosilicate content of 78.1%. After drying, the material is returned to the pyrolysis process for the preparation of silicon tetrafluoride gas.
[0035] Example 2 A method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate, comprising the following steps: (1) Take an industrial grade sodium fluorosilicate sample with a particle size D80 of 120 mesh (after crushing and sieving), activate it at a temperature of 300°C and a vacuum degree of -15kpa to -10kpa for 5 hours, and then weigh 5000g of the sample; take an analytical pure magnesium fluoride sample with a particle size D80 of 280 mesh (after crushing and sieving), activate it at a temperature of 620°C and a vacuum degree of -15kpa to -10kpa for 4 hours, and then weigh 1000g of the sample; (2) After the weighed 5000g sample and 1000g sample were evenly mixed, they were put into a rotary furnace at a rate of 1000g / h for pyrolysis reaction. The rotary furnace was set to a temperature of 645°C, -5kpa~5kpa, and the material stayed in the furnace tube for 2.0h. After the reaction was completed, the solid residual material was cooled to room temperature and weighed to 3097.8g. The sodium fluorosilicate content was 0.12% after sampling and analysis. The solid residual material was loose and had no agglomeration phenomenon, and there was no wall adhesion in the rotary furnace. The generated silicon tetrafluoride gas was collected with an air bag after dust removal and water removal by concentrated sulfuric acid.
[0036] In step (2), the silicon tetrafluoride gas collected by the air bag is first purified by passing through an adsorption column containing 4A molecular sieve and granular activated carbon, and then the gas is introduced into a low-temperature refrigeration device that has been cooled to -115°C. After the intake is completed, the temperature is kept for 2 hours, and then the temperature is slowly raised to -92°C and the gas is collected. Finally, the impurity content is detected by gas chromatography, and the results show that the purity of the silicon tetrafluoride gas is 99.95%.
[0037] (3) Take 700g of solid residual material, add 2400g of pure water to make a suspension, stir at a rate of 50r / min for 1h, then slowly add 6200g of fluorosilicic acid solution, the concentration of fluorosilicic acid solution is 13wt%, the addition time is 3h, continue to stir and react for 3h after the addition is completed, then filter and separate and wash, dry at 120℃ for 3h, weigh 1176.5g after cooling, and take a sample for analysis. XRD analysis shows that the substance is a mixture of sodium fluorosilicate and magnesium fluoride, with a sodium fluorosilicate content of 79.6%. After drying, the material is returned to the pyrolysis process for the preparation of silicon tetrafluoride gas.
[0038] Example 3 A method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate, comprising the following steps: (1) Take an industrial grade sodium fluorosilicate sample with a particle size D80 of 100 mesh (after crushing and sieving), activate it at a temperature of 320°C and a vacuum degree of -20kpa to -10kpa for 7 hours, and then weigh 5000g of the sample; take an analytical pure barium fluoride sample with a particle size D80 of 250 mesh (after crushing and sieving), activate it at a temperature of 550°C and a vacuum degree of -20kpa to -10kpa for 7 hours, and then weigh 1000g of the sample; (2) After the weighed 5000g sample and 1000g sample were evenly mixed, they were put into a rotary furnace at a rate of 1000g / h for pyrolysis reaction. The rotary furnace was set to a temperature of 605℃, -5kpa~5kpa, and the material stayed in the furnace tube for 3.0h. The solid residual material produced after the reaction was cooled to room temperature and weighed to 3207.1g. The sodium fluorosilicate content was 0.59% after sampling and analysis. The solid residual material was loose and had no agglomeration phenomenon, and there was no wall adhesion in the rotary furnace. The silicon tetrafluoride gas produced was collected with an air bag after dust removal and water removal by concentrated sulfuric acid.
[0039] In step (2), the silicon tetrafluoride gas collected by the air bag is first purified by passing through an adsorption column containing 4A molecular sieve and granular activated carbon, and then the gas is introduced into a low-temperature freezing device that has been cooled to -115°C. After the intake is completed, the temperature is kept for 2 hours, and then the temperature is slowly raised to -92°C and the gas is collected. Finally, the impurity content is detected by gas chromatography, and the results show that the purity of the silicon tetrafluoride gas is 99.90%.
[0040] (3) Take 700g of solid residual material, add 2800g of pure water to make a suspension, stir at a rate of 80r / min for 1h, then slowly add 6300g of fluorosilicic acid solution, the concentration of fluorosilicic acid solution is 13wt%, the addition time is 3.5h, continue to stir and react for 4h after the addition is completed, then filter and separate and wash, dry at 115℃ for 3h, weigh 1102.9g after cooling, and take a sample for analysis. XRD analysis shows that the substance is a mixture of sodium fluorosilicate and calcium fluoride, with a sodium fluorosilicate content of 78.5%. After drying, the material is returned to the pyrolysis process for the preparation of silicon tetrafluoride gas.
[0041] Comparative Example 1 (1) Weigh 5000 g of industrial grade sodium fluorosilicate sample with a particle size D80 of 100 mesh (after crushing and screening), and then put it into a rotary furnace at a rate of 1000 g / h for pyrolysis reaction. The parameters set for the rotary furnace are: temperature of 625°C, -10kpa~10kpa, and the residence time of the material in the furnace tube is 2.5 hours. After the reaction is completed, the solid residual material is cooled to room temperature and weighed to be 2796.4 g. Sampling and analysis found that the content of sodium fluorosilicate in the residual material was 35.9%. In addition, it was observed that the solid material formed a large number of hard spherical agglomerates, and the inner wall of the rotary furnace showed a relatively serious adhesion phenomenon. During the continuous pyrolysis process, the furnace tube was blocked and the material could not be discharged. It was necessary to stop the furnace and cool it down, and then apply external force to clear the blockage.
[0042] The collected silicon tetrafluoride gas first passes through an adsorption column filled with 4A molecular sieve and granular activated carbon, and then passes into a low-temperature freezing device frozen to -115°C. After the air intake is completed, it is kept for 2 hours and then slowly heated to -92°C to collect the gas. The impurity content is detected by gas phase, and the silicon tetrafluoride gas content is 99.90%.
[0043] (2) Take 700g of solid residual material, add 2100g of pure water to make a suspension, stir at a rate of 60r / min for 1h, then slowly add 6000g of fluorosilicic acid solution, the concentration of fluorosilicic acid solution is 13wt%, the addition time is 2h, continue to stir and react for 2h after the addition is completed, then filter and separate and wash, dry at 120℃ for 3h, weigh 1106.3g after cooling, and take a sample for analysis. XRD analysis shows that the substance is sodium fluorosilicate, and the sodium fluorosilicate content is 98.2%. After drying, the material is pyrolyzed to prepare silicon tetrafluoride gas.
[0044] Comparative Example 2 (1) Weigh 5000 g of industrial grade sodium fluorosilicate sample with a particle size D80 of 120 mesh (after crushing and screening), and then put it into a rotary furnace at a rate of 1000 g / h for pyrolysis reaction. The parameters set for the rotary furnace are: temperature of 645°C, -5kpa~5kpa, and the residence time of the material in the furnace tube is 2.0 hours. After the reaction is completed, the solid residual material is cooled to room temperature and weighed to 3265.1 g. Sampling and analysis found that the content of sodium fluorosilicate in the residual material was 48.3%. In addition, it was observed that the solid material formed a large number of hard spherical agglomerates, and the inner wall of the rotary furnace showed a relatively serious adhesion phenomenon. During the continuous pyrolysis process, the furnace tube was blocked and the material could not be discharged. It was necessary to stop the furnace and cool it down, and then apply external force to clear the blockage.
[0045] The collected silicon tetrafluoride gas first passes through an adsorption column filled with 4A molecular sieve and granular activated carbon, and then passes into a low-temperature freezing device frozen to -115°C. After the air intake is completed, it is kept for 2 hours and then slowly heated to -92°C to collect the gas. The impurity content is detected by gas phase, and the silicon tetrafluoride gas content is 99.91%.
[0046] (2) Take 870g of solid residual material, add 2400g of pure water to make a suspension, stir at a rate of 50r / min for 1h, then slowly add 6200g of fluorosilicic acid solution, the concentration of fluorosilicic acid solution is 13wt%, the addition time is 3h, continue to stir and react for 3h after the addition is completed, then filter and separate and wash, dry at 120℃ for 3h, weigh 1286.1g after cooling, and take a sample for analysis. XRD analysis shows that the substance is sodium fluorosilicate, and the sodium fluorosilicate content is 98.7%. After drying, the material is pyrolyzed to prepare silicon tetrafluoride gas.
[0047] Comparative Example 3 (1) Weigh 5000 g of industrial grade sodium fluorosilicate sample with a particle size D80 of 100 mesh (after crushing and screening), and then put it into a rotary furnace at a rate of 1000 g / h for pyrolysis reaction. The parameters set for the rotary furnace are: temperature of 605°C, -10kpa~10kpa, and the residence time of the material in the furnace tube is 3.0 hours. After the reaction is completed, the solid residual material is cooled to room temperature and weighed to be 2542.2 g. Sampling and analysis found that the content of sodium fluorosilicate in the residual material was 30.1%. In addition, it was observed that the solid material formed a large number of hard spherical agglomerates, and the inner wall of the rotary furnace showed a relatively serious adhesion phenomenon. During the continuous pyrolysis process, the furnace tube was blocked and the material could not be discharged. It was necessary to stop the furnace and cool it down, and then apply external force to clear the blockage.
[0048] The collected silicon tetrafluoride gas first passes through an adsorption column filled with 4A molecular sieve and granular activated carbon, and then passes into a low-temperature freezing device frozen to -115°C. After the air intake is completed, it is kept for 2 hours and then slowly heated to -92°C to collect the gas. The impurity content is detected by gas phase, and the silicon tetrafluoride gas content is 99.92%.
[0049] (2) Take 650g of solid residual material, add 2800g of pure water to make a suspension, stir at a rate of 80r / min for 1h, then slowly add 6300g of fluorosilicic acid solution, the concentration of fluorosilicic acid solution is 13wt%, the addition time is 3.5h, continue to stir and react for 4h after the addition is completed, then filter and separate and wash, dry at 115℃ for 3h, weigh 1059.21g after cooling, and take a sample for analysis. XRD analysis shows that the substance is sodium fluorosilicate, and the sodium fluorosilicate content is 99.1%. After drying, the material is pyrolyzed to prepare silicon tetrafluoride gas.
[0050] The experimental data and experimental results of the statistical examples and comparative examples are shown in Table 1.
[0051] Table 1 Statistical results
[0052] Figure 1 The XRD patterns of the solid residue material in step (2) of Example 1 and the mixture after the solid residue material in step (3) reacts with the fluorosilicic acid solution. Figure 1It can be seen that in Example 1, after adding the auxiliary agent calcium fluoride, the solid residual material is a mixture of sodium fluoride and calcium fluoride, and the characteristic peak of sodium fluorosilicate is not observed, indicating that the sodium fluorosilicate in the raw material has been basically completely decomposed. In addition, the mixture after the solid residual material reacts with the fluosilicic acid solution is a mixture of calcium fluoride and sodium fluorosilicate, but does not show an obvious characteristic peak of sodium fluoride, which indicates that the sodium fluoride is also basically completely reacted. These findings are consistent with theoretical predictions.
[0053] Figure 2 The XRD patterns of the solid residue material in step (2) of Example 2 and the mixture after the solid residue material in step (3) reacts with the fluorosilicic acid solution. Figure 2 It can be seen that in Example 2, after adding the auxiliary agent magnesium fluoride, the solid residual material is a mixture of sodium fluoride and magnesium fluoride, and the characteristic peak of sodium fluorosilicate is not observed, indicating that the sodium fluorosilicate in the raw material has been substantially completely decomposed. In addition, the mixture after the solid residual material reacts with the fluosilicic acid solution is a mixture of magnesium fluoride and sodium fluorosilicate, but does not show an obvious characteristic peak of sodium fluoride, which indicates that the sodium fluoride is also substantially completely reacted. These findings are consistent with theoretical predictions.
[0054] Figure 3 The XRD patterns of the solid residue material in step (2) of Example 3 and the mixture after the solid residue material in step (3) reacts with the fluorosilicic acid solution. Figure 3 It can be seen that in Example 3, after adding the auxiliary agent barium fluoride, the solid residual material is a mixture of sodium fluoride and barium fluoride, and the characteristic peak of sodium fluorosilicate is not observed, indicating that the sodium fluorosilicate in the raw material has been basically completely decomposed. In addition, the mixture after the solid residual material reacts with the fluosilicic acid solution is a mixture of barium fluoride and sodium fluorosilicate, but does not show an obvious characteristic peak of sodium fluoride, which indicates that the sodium fluoride is also basically completely reacted. These findings are consistent with theoretical predictions.
[0055] Figure 4 The XRD patterns of the solid residue material in step (1) of comparative example 1 and the mixture after the solid residue material in step (2) reacts with the fluorosilicic acid solution. Figure 4 It can be seen that in Comparative Example 1, without adding an auxiliary agent, the pyrolysis residue is a mixture of sodium fluoride and sodium fluorosilicate, indicating that a large amount of sodium fluorosilicate in the raw material is not completely decomposed; the mixture after the solid residual material reacts with the fluorosilicic acid solution is mainly sodium fluorosilicate, without obvious sodium fluoride characteristic peaks, indicating that the sodium fluoride is almost completely reacted. Compared with Example 1, without adding an auxiliary agent, the decomposition efficiency of the raw material is lower, which is consistent with the theoretical prediction.
[0056] Figure 5The XRD patterns of the solid residue material in step (1) of comparative example 1 and the mixture after the solid residue material in step (2) reacts with the fluorosilicic acid solution. Figure 5 It can be seen that in Comparative Example 2, without adding an auxiliary agent, the pyrolysis residue is a mixture of sodium fluoride and sodium fluorosilicate, indicating that a large amount of sodium fluorosilicate in the raw material is not completely decomposed; the mixture after the solid residual material reacts with the fluorosilicic acid solution is mainly sodium fluorosilicate, without obvious sodium fluoride characteristic peaks, indicating that the sodium fluoride is almost completely reacted. Compared with Example 2, without adding an auxiliary agent, the decomposition efficiency of the raw material is lower, which is consistent with theoretical predictions.
[0057] Figure 6 The XRD patterns of the solid residue material in step (1) of comparative example 1 and the mixture after the solid residue material in step (2) reacts with the fluorosilicic acid solution. Figure 6 It can be seen that in Comparative Example 3, without adding an auxiliary agent, the pyrolysis residue is a mixture of sodium fluoride and sodium fluorosilicate, indicating that a large amount of sodium fluorosilicate in the raw material is not completely decomposed; the mixture after the solid residual material reacts with the fluorosilicic acid solution is mainly sodium fluorosilicate, without obvious sodium fluoride characteristic peaks, indicating that the sodium fluoride is almost completely reacted. Compared with Example 3, without adding an auxiliary agent, the decomposition efficiency of the raw material is lower, which is consistent with the theoretical prediction.
[0058] Figure 7 This is a photo of the solid residue in step (2) of Example 1.
[0059] Figure 8 This is a photo of the solid residual material in step (1) of comparative example 1.
[0060] contrast Figure 7 and Figure 8 We can clearly see that by adding additives, the solid residue obtained is loose and has no agglomeration phenomenon, thus solving the problem of sticking to the wall in the rotary kiln.
[0061] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate, characterized in that: The steps include: (1) Sodium fluorosilicate and the additive are crushed and sieved separately, and then activated at 250-620°C; (2) The activated sodium fluorosilicate and the auxiliary agent are mixed and subjected to a pyrolysis reaction to obtain a crude silicon tetrafluoride product and residual solids; and the crude silicon tetrafluoride product is purified to obtain a silicon tetrafluoride product.
2. The method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate according to claim 1, characterized in that: The auxiliary agent in step (1) is any one or more of calcium fluoride, magnesium fluoride, barium fluoride, white carbon black and silicon carbide.
3. The method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate according to claim 1, characterized in that: The sodium fluorosilicate in step (1) is crushed and then passed through a 60-120 mesh sieve; The additive in step (1) is crushed and passed through a 200-300 mesh sieve.
4. The method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate according to any one of claims 1 to 3, characterized in that: The activation treatment pressure in step (1) is -20 kPa to -10 kPa (G), and the activation treatment time is 3 to 8 hours.
5. The method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate according to claim 1, characterized in that: In step (2), the activated sodium fluorosilicate and the auxiliary agent are mixed in a mass ratio of 4 to 5:
1.
6. The method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate according to claim 1, characterized in that: The conditions of the pyrolysis reaction in step (2) are: pyrolysis temperature of 550-650° C., reaction pressure of -10 kPa-10 kPa (G), and pyrolysis time of 1.5-3.0 h.
7. The method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate according to claim 1, characterized in that: The residual solid is prepared into a suspension, and the fluorosilicic acid solution is added and stirred for reaction. The sodium fluorosilicate obtained by filtering, washing and drying is then reused in step (1).
8. The method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate according to claim 7, characterized in that: The specific operation of preparing the residual solid into a suspension includes: mixing the residual solid with water in a mass ratio of 1:2.5-4 to prepare a suspension.
9. The method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate according to claim 8, characterized in that: The mass ratio of the fluorosilicic acid solution to the residual solid is 8-12:1; The concentration of the fluorosilicic acid solution is 10-15wt%; The addition of the fluorosilicic acid solution is completed within 2 to 5 hours.
10. The method for preparing silicon tetrafluoride by pyrolysis of sodium fluorosilicate according to claim 7, characterized in that: The drying temperature is 100-150°C and the drying time is 3-6 hours; The stirring reaction speed is 40-90 r / min, and the stirring reaction time is 3-6 h.
Citation Information
Patent Citations
Method for preparing silicon tetrafluoride through pyrolysis of sodium fluosilicate in rotary reaction furnace
CN101698482A
Method for preparing silicon tetrafluoride and anhydrous hydrogen fluoride from sodium fluosilicate acidified by sulfuric acid
CN101948114A
Production method of silicon tetrafluoride
CN111039293A